Telling stories in science communication: case studies of scholar-practitioner collaboration - Riedlinger, M. (2020)
Reflecting on the practice of storytelling, this practice insight explores how collaborations between scholars and practitioners can improve storytelling for science communication outcomes with publics. The case studies presented demonstrate the benefits of collaborative storytelling for inspiring publics, promoting understanding of science, and engaging publics more deliberatively in science. The projects show how collaboration between scholars and practitioners [in storytelling] can happen across a continuum of scholarship from evaluation and action research to more critical thinking perspectives. They also show how stories of possible futures and community efficacy can support greater engagement of publics in evidence-informed policymaking. Storytelling in collaborations between scholars and practitioners involves many activities: combining cultural and scientific understandings; making publics central to storytelling; equipping scientists to tell their own stories directly to publics; co-creating stories; and retelling collaborative success stories. Collaborative storytelling, as demonstrated in these case studies, may improve the efficacy of science communication practice as well as its scholarship.